2021
DOI: 10.1186/s12938-021-00892-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of the characteristics of joint motion and gait pattern in a rodent model following spinal nerve ligation

Abstract: Background The spinal nerve ligation (SNL) rat is well known as the most common rodent model of neuropathic pain without motor deficit. Researchers have performed analyses using only the von Frey and thermal withdrawal tests to evaluate pain intensity in the rat experimental model. However, these test are completely different from the neurological examinations performed clinically. We think that several behavioral reactions must be observed following SNL because the patients with neuropathic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The handheld algometer we used calculates PPTs on super cial tissue that equate to one point of skin tenderness as found clinically when assessing a painful area [16][17][18][19][20]. It also includes measures of temporal summation by wind-up and documentation of dynamic mechanical allodynia [18][19][20][21][22][23]. When appropriate standards are applied, PPTs can provide important and unique information about the functional status of the somatosensory system, which would complement already existing clinical methods [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The handheld algometer we used calculates PPTs on super cial tissue that equate to one point of skin tenderness as found clinically when assessing a painful area [16][17][18][19][20]. It also includes measures of temporal summation by wind-up and documentation of dynamic mechanical allodynia [18][19][20][21][22][23]. When appropriate standards are applied, PPTs can provide important and unique information about the functional status of the somatosensory system, which would complement already existing clinical methods [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of PPTs were reported previously in the study of LBP in western countries [5,15,[17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. All of the studies used healthy control data to compare with the data of the patients with LBP [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. PPT data using manual/electronic pressure algometry and cross-friction algometry in healthy control subjects from the lower back and QC or hip, gluteus maximus, or femur were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal nerve ligation (SNL) is a model for simulating spinal nerve injury, which shows typical pNP manifestations, such as spontaneous pain, thermal hyperalgesia, mechanical hyperalgesia, etc. (Seto et al, 2021). A study showed that 14 days after modeling, the mRNA expression of TLR4, IRAK1, and TRAF6 were significantly increased in SNL rats, and the expression levels of TNF-α and IL-6 also increased.…”
Section: Tuina Exerts Analgesic Effects By Suppressing Peripheral Inf...mentioning
confidence: 99%
“…Spinal nerve ligation (SNL) is another model of neuropathic pain, developed by Kim and Chung (1992) , where the L5 and L6 spinal nerves are tightly ligated and also produce significant mechanical allodynia. This procedure requires high technical skill to avoid damage to the L4 nerve which can abolish allodynia and cause motor deficits ( Challa, 2015 ; Seto et al, 2021 ). This model has been used in rats to indicate glycinergic neurotransmission in the pathophysiology of pain, whereby oral or S.C. administration of the GlyT2 inhibitor opiranserin reduced mechanical allodynia in the von Frey assay ( Pang et al, 2012 ).…”
Section: Pain Modelsmentioning
confidence: 99%